The Principle of Territoriality of IP Rights - V. V. Pirogova (Московский журнал международного права, 2011)
The article is dedicated to the principle of the territoriality of IP rights of Intellectual property law. The article pays special attention to the problem of conflict of laws and Intellectual Property Rights and analyses some of international conventions.